Poxviral protein E3-altered cytokine production reveals that DExD/H-box helicase 9 controls Toll-like receptor-stimulated immune responses. - Bowie, Andrew; Carty, Michael (My University, 2018)
Host pattern recognition receptors (PRRs) such as Toll-like receptors (TLRs) detect viruses and other pathogens, inducing production of cytokines that cause inflammation and mobilize cells to control infection. Vaccinia virus (VACV) encodes proteins that antagonize these host innate immune responses, and elucidating the mechanisms of action of these viral proteins helped shed light on PRR signaling mechanisms. The VACV virulence factor E3 is one of the most intensely studied VACV proteins and has multiple effects on host cells, many of which cannot be explained by the currently known cellular targets of E3. Here, we report that E3 expression in human monocytes alters TLR2- and TLR8-dependent cytokine induction, and particularly inhibits interleukin (IL)-6. Using MS, we identified DExD/H-box helicase 9 (DHX9) as an E3 target. Although DHX9 has previously been implicated as a PRR for sensing nucleic acid in dendritic cells, we found no role for DHX9 as a nucleic acid-sensing PRR in monocytes. Rather, DHX9 suppression in these cells phenocopied the effects of E3 expression on TLR2- and TLR8-dependent cytokine induction, in that DHX9 was required for all TLR8-dependent cytokines measured, and for TLR2-dependent IL-6. Furthermore, DHX9 also had a cell- and stimulus-independent role in IL-6 promoter induction. DHX9 enhanced NF-κB-dependent IL-6 promoter activation, which was directly antagonized by E3. These results indicate new roles for DHX9 in regulating cytokines in innate immunity and reveal that VACV E3 disrupts innate immune responses by targeting of DHX9.
PUBLISHED
Keywords: DExD/H-box helicase (DHX9); Immune evasion; NF-κB (NF-KB); host-pathogen interaction; innate immunity; interleukin 6 (IL-6); pattern recognition receptor (PRR); poxvirus; signal transduction; toll-like receptor (TLR)